Environmental Impacts of Orphaned and Abandoned Wells: Methane Emissions, and Implications for Carbon Storage - Ahmed Alsubaih; Kamy Sepehrnoori; Mojdeh Delshad (Applied Sciences)
Orphaned and abandoned wells in the United States pose significant environmental risks, including methane emissions, groundwater contamination, and ecosystem degradation. These wells also threaten the integrity of carbon capture and storage (CCS) projects by providing potential leakage pathways for stored CO2, particularly if they lack proper plugging and well integrity. Although the exact number of orphaned and abandoned wells is uncertain due to poor historical documentation, recent estimates suggest there could be as many as 3.9 million such wells nationwide, emitting approximately 3.2 Teragram (Tg) of methane annually. This study investigates the distribution of orphaned and abandoned wells across the United States, presenting new estimates of documented wells and exploring their methane emissions. Through state-level data analysis, the number of documented orphan wells is estimated to be significantly higher than previously reported. A machine learning model, specifically a RandomForestRegressor, was employed to predict the locations of potential orphan wells, enhancing the ability to target monitoring and remediation efforts.